H2-Driven Reduction of Flavin by Hydrogenase Enables Cleaner Operation of Nitroreductases for Nitro-Group to Amine Reductions - Ramirez, Miguel A.; Joseph Srinivasan, Shiny; Cleary, Sarah E.; Todd, Peter M. T.; Reeve, Holly A.; Vincent, Kylie A. (Frontiers in Catalysis, 2022)
Hydrogenase-mediated reduction of flavin mononuclotide by H2 is exploited to enable cleaner application of nitroreductase enzymes for reduction of aromatic nitro functional groups. This turns the overall reaction into a biocatalytic hydrogenation. Use of flavin-containing nitroreductases in industrial biotechnology typically relies upon NADH or NADPH as reductant, together with glucose dehydrogenase and glucose as a regeneration system for the reduced nicotinamide cofactor, with 3 equivalents of the carbon-intensive glucose required for a single 6-electron nitro to amine conversion. We show here that reduced flavin mononucleotide is an alternative reductant for nitroreductases, and by combining this with H2-driven recycling of reduced flavin, we avoid glucose, thereby enabling atom-efficient biocatalytic nitro reductions. We compare this biocatalytic system, via green chemistry metrics, to existing strategies for biocatalytic nitro-group reductions, particularly with respect to replacing glucose with H2 gas. We take steps towards demonstrating industrial viability: we report an overexpression system for E. coli hydrogenase 1, giving a 12-fold improvement in enzyme yield; we show a reaction in which the hydrogenase exhibits >26,000 enzyme turnovers; and we demonstrate reasonable solvent tolerance of the hydrogenase and flavin reduction system which would enable reaction intensification.